A re-evaluation of the role of inhaled corticosteroids in the management of patients with chronic obstructive pulmonary disease. (August 2015) - D'Urzo, Anthony; Donohue, James F; Kardos, Peter; Miravitlles, Marc; Price, David
<x xml:space="preserve">Abstract</x> Introduction: Inhaled corticosteroids (ICS) (in fixed combinations with long-acting β2-agonists [LABAs]) are frequently prescribed for patients with chronic obstructive pulmonary disease (COPD), outside their labeled indications and recommended treatment strategies and guidelines, despite having the potential to cause significant side effects. Areas covered: Although the existence of asthma in patients with asthma–COPD overlap syndrome (ACOS) clearly supports the use of anti-inflammatory treatment (typically an ICS/LABA combination, as ICS monotherapy is usually not indicated for COPD), the current level of ICS/LABA use is not consistent with the prevalence of ACOS in the COPD population. Data have recently become available showing the comparative efficacy of fixed bronchodilator combinations (long-acting muscarinic antagonist [LAMA]/LABA with ICS/LABA combinations). Additionally, new information has emerged on ICS withdrawal without increased risk of exacerbations, under cover of effective bronchodilation. Expert opinion: For patients with COPD who do not have ACOS, a LAMA/LABA combination may be an appropriate starting therapy, apart from those with mild disease who can be managed with a single long-acting bronchodilator. Patients who remain symptomatic or present with exacerbations despite effectively delivered LAMA/LABA treatment may require additional drug therapy, such as ICS or phosphodiesterase-4 inhibitors. When prescribing an ICS/LABA, the risk:benefit ratio should be considered in individual patients.